Disposal practices of cigarettes and electronic nicotine products among adults, findings from Wave 6 (2021) of the PATH Study - Eva Sharma; Johanna Dubsky; Katherine V. Garcia-Rosales; Michael Halenar; Adam F. Benson; Alexander Maki; Andrea L. Ruybal; Aura Lee Morse; Michael D. Sawdey; Rudaina Alrefai-Kirkpatrick; Silvana Skara; Susana Addo Ntim; et al. (PLoS ONE, 2025)
Background Tobacco product waste is environmentally hazardous but preventable. Therefore, it is important to understand tobacco disposal behaviors among those using tobacco products. Objectives To explore self-reported disposal practices of cigarette butts and electronic nicotine products (ENP) components among adults (aged 18+). Methods We used nationally representative cross-sectional data from Wave 6 (2021; n = 29,516) of the Population Assessment of Tobacco and Health (PATH) Study among adults who used cigarettes (manufactured and/or roll-your-own) and/or ENP every day, some days, or in the past 30 days. Results In 2021, 89.7% (95% CI: 88.7, 90.6) of adults who smoked manufactured cigarettes usually disposed of cigarette butts in landfills (in an ash tray, in a cigarette disposal, or in the trash). Most adults who usually disposed of butts in landfills smoked daily (73.1%; 95% CI: 71.3, 74.9) and smoked an average of 14.6 cigarettes per day. Among those who used ENP, most adults usually disposed of the components in landfills (disposable devices: 83.1%; 95% CI: 80.5, 85.4; empty pods and cartridges: 85.4%; 95% CI: 82.4, 87.9; coils and atomizers: 71.2%; 95% CI: 68.1, 74.1; batteries: 48.5%; 95% CI: 45.2, 51.9; e-liquid containers: 70.9%; 95% CI: 67.1, 74.5; and leftover or unused e-liquid: 50.5%; 95% CI: 45.8, 55.2). Recycling as a usual practice was limited for people who used ENP- for disposable devices: 6.0% (95%CI: 4.6, 7.8); empty pods and cartridges: 5.0% (95% CI: 3.7, 6.8); coils and atomizers: 11.7% (95% CI: 9.4, 14.5); batteries: 23.7% (95% CI: 20.9, 26.8); and e-liquid containers: 18.0% (95% CI: 15.1, 21.3). Discussion These findings demonstrate the large scope of tobacco product waste disposal in the United States and may inform efforts to address tobacco product waste management, such as environmental impact assessments and consumer education about proper disposal of tobacco products.